A study to evaluate the relationship between serum vitamin d level and chronic rhinosinusitis - Sahni, Dimple; Bagri, Deepika; Bhagat, Sanjeev; Sharma, Dinesh; Singh, Jasvir (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Chronic rhinosinusitis (CRS) places a relatively large socioeconomic burden on developed nations, yet remains a difficult disease to treat. Vitamin D3 (VD3) deficiency is reported to be associated with increased incidence of allergic airway diseases. The ability of VD3 to augment innate and adaptive immune responses has sparked interest in its immunologic role in allergy. The objective of the present study is to evaluate the relationship between serum vitamin D level and chronic rhinosinusitis. Methods: Total 90 patients were included in the study and divided into three groups i.e., 30 patients of chronicrhinosinusitis with nasal polyposis (CRSwNP), 30 patients of chronic rhinosinusitis without nasal polyposis (CRSsNP) and 30 healthy subjects were used as control. The severity of CRSwNP was assessed with the Lund-Mackay (LM) score and polyp grading system. VD3 status was assessed by measuring circulating 25-hydroxyvitamin D (25OHD) by using ELISA. Results: Serum 25OHD levels (ng/ml±SD) were significantly lower in patients with CRSwNP (16.16±8.86) than in those with CRSsNP (23.28±5.35; p=0.001) and control 44.37±19.87. The incidence of vitamin D deficiency (<20 ng/ml) in CRSwNP and CRSsNP patients were 60% and 20%; however, the incidence of vitamin D insufficiency (20-30 ng/ml) in these patients were 37% and 70%, respectively. A significantly inverse relationship was found between serum 25OHD level and polyp grade (p=0.048), indicating lower serum 25OHD was associated with higher polyp grade. Serum 25OHD was inversely related to both LM endoscopic and LM CT scan score, which is found to be significant (p=0.001). Conclusions: The available evidence indicates that there is a significant relationship between low VD3 levels and CRSwNP phenotype. Lower 25VD3 levels were associated with more severe mucosal inflammation on nasal endocscoy and CT scan.